Evaluation of Prescribing Practices in the Outpatient Departments of a Teaching Hospital - Paul, PC; Pal, DR; Rahaman, MM; Islam, MJ; Siddique, AR (Bangladesh Medical Journal, 2014)
Irrational use of medicines is widespread throughout the world. Polypharmacy, injudicious use of antimicrobials and unnecessary use of vitamins are commonly observed. In an attempt to observe the prescribing practices in a Teaching Hospital outpatient departments and to sensitize the future prescribers about rational prescribing, 1200 prescriptions were collected and analyzed by 4th year MBBS students using some of the WHO/INRUD core drug prescribing indicators. The average number of drug per prescription was 3.24. Only 0 13% drugs prescribed under generic names. Around 36.83% of prescriptions were prescribed with antimicrobials and 7.08% prescriptions were contained injections. About 48.35 drugs were prescribed from essential list of drugs and vitamins were prescribed in 33.33% prescriptions. The result revealed that there are apparent lacks of prescribing habit among the prescribers even in a teaching hospital. It is suggested that the periodic evaluation of prescribing practices at a health facility would eventually help to promote rational prescribing. Furthermore, participation of 4th year MBBS students in such exercise may enhance the understanding and sensitize them about rational use of medicines in future. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18499 Bangladesh Medical Journal 2011 Vol.40(2): 19-22